The Role of the Supreme Court of Calcutta (1774) in Shaping Early Colonial Jurisprudence - Sheikh, Md. Ibrahim Hussain; Kesharwani, Pradeep Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Established in 1774 under the provisions of the Regulating Act of 1773, the Supreme Court of Judicature at Fort William in Calcutta was the first apex judicial institution in British India. Its creation marked a crucial turning point in the legal history of colonial India, introducing formal English legal principles into a pluralistic society governed by indigenous laws and customs. This paper examines the Supreme Court's institutional role in shaping early colonial jurisprudence, focusing on its legal authority, jurisdictional conflicts, landmark cases, and long-term implications on the Indian legal system. Through a historical-legal analysis, the study argues that the Court played a dual role—as an instrument of imperial authority and as a site of legal contestation between British legal norms and native institutions. The legacy of the Supreme Court of Calcutta laid the foundational framework for the evolution of India's colonial judiciary and its eventual integration into modern constitutional governance.